Genetic diversity and population structure of Canarian chicken using microsatellite DNA markers - Amado Manuel Canales Vergara; Alexandr Torres Krupij; María del Rosario Fresno Baquero; Martina Macrì; Juan Vicente Delgado Bermejo; Amparo Martínez Martínez (Italian Journal of Animal Science)
The Canary Islands have historically been a crossway among at least three continents; therefore, the genetic influences on their local animal breeds have been extremely diverse. In the Canarian chicken population, genetic diversity is evident but it has never been studied. The aim of this study was to assess the population structure and genetic diversity within the Canarian chicken population, as well as between the Canarian chicken population, the Spanish local populations, and the commercial chicken populations with microsatellites, with a view to reinforce the official recognition of the breed, for the design and development of a conservation program. Blood samples were collected at random from 198 animals of the Canarian and compared with Spanish local and commercial strains, in order to determine differentiation and genetic relatedness. The five phenotypic varieties of Canarian chicken, the population structure and genetic diversity within the Canarian chicken population had a higher unbiased expected heterozygosity than the observed heterozygosity. Comparing the Canarian vs other local Spanish breeds and commercial strains, FST was relatively high (0.179) (0.164 – 0.195), the neighborhood network showed that the Canarian varieties did not cluster with the other Spanish breeds. The STRUCTURE, confirmed that the Rubilana variety differed from the other four Canary Islands. We conclude that the Canary Islands chicken population shows a differentiated genetic profile, versus other Spanish and cosmopolitan breeds. The theory that the existence of genetic varieties is based on the color of feathers was definitively discarded, except in the Rubilana population, which could be admitted as a genetically different variety.